Comparative Study of Effectiveness Between Azithromycin and Levofloxacin in the Treatment of Childhood Typhoid Fever - Rahat, Sayeda Farzana; Shaha, Kartick Chanda; Sultana, Humayra; Rahman, Md Shafiqur; Rahman, Mohammad Mahfuzur (Journal of Dhaka National Medical College & Hospital, 2023)
Abstract Background: Typhoid fever is an important cause of morbidity and mortality in patients especially in developing country. Therapy with conventional drugs is associated with increasing resistance, non-compliance to therapy and toxicity. Objective: The aim of this study was to compare the effectiveness of Azithromycin and levofloxacin in the treatment of childhood typhoid fever. Methods: This comparative study was carried out among 120 patients presenting with symptoms, signs and laboratory investigations diagnostic of typhoid fever in IPD and OPD of Paediatric Department, Dhaka National Medical College Hospital, Dhaka, from April to October 2013. Patients received Levofloxacin (n-60) consider as group I and Azithromycin (n-60) consider as group II. Widal test positive was included for the study & specific antibiotic (Levofloxacin or Azithromycin) treatment was started by randomization using lottery method. Statistical analysis of the results were obtained by using window based computer software devised with Statistical Packages for Social Sciences (SPSS-20.1). Results: Majority of the patients time of afebrile after taking antibiotic was 6 days in group I (n=21, 35.0%) whereas it was 4 days in group II (n=23,38.3%). The difference was not statistically significant (p>0.05) between two groups. Almost two third 68.33% of the patients in group I and 100.0% in group II patients were receiving treatment for 7 days. Regarding the side effects, it was observed that nearly three fourth (73.3%) of the patients in group I and 45(75.0%) in group II patients had nausea. Vomiting was found 8(13.3%) and 4(6.7%) in group I and group II respectively. Diarrhoea was 2(3.3%) in group I and 13(21.7%) in group II. Abdominal discomfort was 17(28.3%) in group I and 13(21.7%) in group II. The difference was not statistically significant (p>0.05) between two groups. Conclusion: Both drugs are equally effective in the treatment of childhood typhoid fever. Considering duration of treatment Azithromycin is better than levofloxacin. J. Dhaka National Med. Coll. Hos. 2023; 29 (02): 28-31